2007
DOI: 10.1523/jneurosci.3110-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Can the Human Brain Predict the Consequences of Arm Movement Corrections When Transporting an Object? Hints from Grip Force Adjustments

Abstract: It is well established that motor prediction is crucial for many of our daily actions. However, it is still unclear whether the brain generates motor prediction in real time. To challenge this idea, grip force was monitored while subjects had to transport a hand-held object to a visual target that could move unexpectedly. In agreement with previous reports, subjects triggered fast arm movement corrections to bring the object to the new target location. In addition, we found that subjects initiated grip force a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 34 publications
7
46
2
Order By: Relevance
“…However, this dichotomy does not occur with MF adaptation, because MF is insensitive to environmental variability. Our findings also provide explanations for previous results showing that GFs are paradoxically increased following initial exposure to microgravity (Augurelle et al, 2003) and that real-time feedback responses can lead to increased GF following sudden, unexpected increases or decreases in LF (Danion, 2007). These results mirror the current findings, and suggest that variability-driven changes in GF control govern real-time feedback responses as well as feedforward motor adaptation.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…However, this dichotomy does not occur with MF adaptation, because MF is insensitive to environmental variability. Our findings also provide explanations for previous results showing that GFs are paradoxically increased following initial exposure to microgravity (Augurelle et al, 2003) and that real-time feedback responses can lead to increased GF following sudden, unexpected increases or decreases in LF (Danion, 2007). These results mirror the current findings, and suggest that variability-driven changes in GF control govern real-time feedback responses as well as feedforward motor adaptation.…”
supporting
confidence: 91%
“…Moreover, the strength of on-line movement corrections has been shown to depend both on the certainty associated with sensory information and one's prior beliefs about the environment in a manner consistent with Bayesian integration (Körding and Wolpert, 2004;Körding et al, 2004;Franklin et al, 2012). This integration often occurs without awareness as simple neural computations can provide the required variability estimates Kepecs et al, 2008;Kiani and Shadlen, 2009;Kepecs and Mainen, 2012;De Martino et al, 2013). For example, variability estimates like the ones used in the ACEVU model can arise from a simple trial-by-trial update rule, whereby the current estimate of variability can be expressed as a weighted combination of the previous variability estimate and a rectified version of current sensory information (Eqs.…”
Section: Uncertainty-driven Control Of Gfs and Muscular Cocontractionmentioning
confidence: 99%
“…This involves a feed-forward regulation requiring the use of sensorimotor memory, as grip force parameters, such as object weight and friction between skin and object surface, are recalled from previous experience (Johansson et al , 1988, Danion et al , 2007.…”
Section: Als Hand Function and Mirror Neuronsmentioning
confidence: 99%
“…Several behavioural studies have demonstrated anticipatory and adaptive mechanisms in human sensory-motor control based on internal models underlying tasks such as eye-hand coordination (Ariff et al, 2002;Nanayakkara & Shadmehr, 2003;Kluzik et al, 2008), object manipulation (Johansson, 1998;Witney et al, 2004;Danion & Sarlegna, 2007), eye movements (Barnes & Asselman, 1991), balance control (Huxham et al, 2001), and locomotion (Grasso et al, 1998), as described in the following subsections.…”
Section: Behavioral Evidencesmentioning
confidence: 99%
“…Feedback is not only essential for the acquisition of the internal model, but constant uninterrupted feedback is also necessary to maintain previously acquired forward models. In analyzing whether the human brain anticipates in real time the consequences of movement corrections, Danion and Sarlegna (2007) monitored grip force while subjects transported a hand-held object to a visual target that could move unexpectedly. They found that subjects triggered fast arm movement corrections to bring the object to the new target location, and initiated grip force adjustments before or in synchrony with arm movement corrections.…”
Section: Object Manipulationmentioning
confidence: 99%